Meta-Analysis: The Influence of Knowledge, Hormonal Contraceptive Use, and Sexually Transmitted Disease on Cancer Screening Uptake - Diani Fadmi Putri; Andri Setiawan; Nathanael Aditya Santoso; Bhisma Murti; Nindita Arum Veibiani (Journal of Epidemiology and Public Health, 2025)
Background: Cervical cancer is still the most common problem among women. Prevention of cervical cancer can be done prospectively through human papillomavirus (HPV) vaccination and screening or early diagnosis. Screening is essential to reduce the incidence and death of cervical cancer. This study aims to analyze and estimate the influence of knowledge, the use of hormonal contraceptives, and the history of sexually transmitted diseases on cervical cancer screening. Subject and Method: This study is a meta analysis using the PRISMA flowchart and the PICO model. Population: women of childbearing age. Intervention: using hormonal contraceptives, having good cervical cancer knowledge, and having a history of sexually transmitted infections. Comparation: not using hormonal contraceptives, poor cervical cancer knowledge and no history of sexually transmitted infections. Outcome: cervical cancer screening. The process of searching for articles by searching through databases in Google scholar, Scopus, ProQuest, PubMed, Elsevier, and Science direct. The keywords used are "hormonal contraception" OR "pill" OR "injection" OR "implant" AND "Cervical cancer screening" OR "sexually transmitted infection" OR "HIV" OR "STD" OR "syphilis" OR "gonorrhea" AND "cancer knowledge" AND "cross sectional" AND "aOR". Articles are selected based on inclusion criteria, namely multivariate articles with a cross sectional design  published in 2014-2024. Data analyzed using Revman 5.3. Results: A meta analysis was conducted on 15 primary studies from Ethiopia, Cambodia, and Uganda. The results showed that the use of cervical cancer screening increased with good knowledge (aOR= 2.03; CI 95%= 1.70 to 2.43; p<0.001), use of hormonal contraceptives (aOR= 1.83 CI 95%= 1.70 to 1.96; p<0.001), and history of sexually transmitted diseases (aOR= 2.32; CI 95%= 1.81 to 2.97; p<0.001). Conclusion:  Good knowledge, use of hormonal contraceptives, and history of infectious diseases increase the use of cervical cancer screening performance